THE “TRAPS” OF COMMUNITY AND THE POWER OF THE DISINTEREST IN THE PERSPECTIVE OF BOURDIEU - Bialakowsky, Alejandro (Centro de Investigaciones y Estudios sobre Cultura y Sociedad, 2015)
This article intends to analyze the “traps” of community in Bourdieu´s perspective. For that, firstly, it indicates the legacy of Tönnies for sociology around the tie between community and disinterested relationships (past, few in the present and emancipatory in the future). Secondly, it tracks the deep critiques of Bourdieu to this legacy, from his study of the “interest into disinterest” framed on his reflections about social domination and its euphemisms. In this, his interpretation both of non modern societies, and of the modern disinterest of the State with universal pretentions (for example, in the official language and in education), and of autonomized and disinterested fields of symbolic goods, which include sociology, can be observed. In the last instance, in the final works of Bourdieu the “traps” which community contains emerge. There, he advocates for an explicit political intervention in which communitarian and disinterested topics appear, for example in his call for the collaboration between activists and intellectuals. Then, a tension becomes clear in the author between a critical and reflexive sociology and social emancipation. Thereby, this article aims to contribute to a theory of community and of social domination, which has suggestive implications for the present.